Pengaruh Gerakan Hindutva terhadap Hubungan Bilateral India-Pakistan Era Kepemimpinan Narendra Modi (2014-2022) - Sukma, Feby Melati; Asy’ari, Muh. (Journal of International and Local Studies, 2024)
Abstract: Hindutva is a political ideology that supports Hindu supremacy in India which aims to transform India as a secular state into an ethno-Nationalist State (ethnic nationalism). The revival of Hindutva politics in India began since the Bharatiya janata Party (BJP) which embraced the Hindutva ideology took over the central government of India in 2014. As an ideology, Hindu nationalism (Hindutva) has dramatically changed Indian politics and its relations with other countries, especially Pakistan with the help of Narendra Modi. Therefore, this study aims to find out the influence of the Hindutva movement on India-Pakistan bilateral relations during the era of Narendra Modi's leadership. This study used descriptive qualitative research methods with library research data collection techniques. The analysis in this study uses two concepts, namely the concept of bilateral relations and the concept of political ideology. The results of this study indicate that the emergence of the Hindutva movement as a political ideology in India has brought more serious strains on the bilateral relations between India and Pakistan.  Keywords: India, Pakistan, Hindutva, Political Ideology, Bilateral relations.